Six years' experience with the discontinuation of BCG vaccination. 4. Protective effect of BCG vaccination against the Mycobacterium avium intracellulare complex - Trnka, L; Danková, D; Svandová, E (Tubercle and lung disease, 1994)
SETTING: In 1986, mass BCG vaccination of newborns was discontinued in an extensive territorial sample of neonates in the Czech Republic (30,000 infants annually). The non-vaccinated children have since been tuberculin tested at two-year intervals; those with continual or repeated intensive contact with animals in households or on farms were also tested with Mycobacterium avium intracellulare complex sensitin in addition to tuberculin. OBJECTIVE: Within the frame work of the surveillance programme the incidence of infection and disease caused by M. avium intracellulare complex (M. avium complex) was evaluated and the protective effect of BCG vaccination analysed. DESIGN: In 1986-93, out of 190,874 non-vaccinated children, 36 were found to be infected by M. avium complex; 27 of them developed disease, i.e. mycobacteriosis other than tuberculosis (MOTT). RESULTS: The annual risk of infection with M. avium complex was 4.8/100,000 children per year, of whom 3.6/100,000 developed mycobacteriosis. 24 patients suffered from swelling of cervical lymph nodes, 2 of mediastinal lymph nodes and one child had the disease localized both in cervical and mediastinal lymph nodes. The disease was verified bacteriologically in 9 children. Most of the diseased children had impaired immunity; a marked skin reactivity of M. avium complex sensitin was present in all infected children. Animal sources infected by M. avium complex were detected in 5 cases. Another 14 children also had close contact with animals but without proven M. avium complex infection. CONCLUSION: In non-BCG vaccinated children the incidence of lymphadenitis caused by M. avium complex was considerably higher than in vaccinated children. BCG cells possess antigenic determinants which confer protective immunity probably both against M. tuberculosis and against M. avium complex infections. It may thus be assumed that BCG vaccination protects both against pathogenic tubercle bacilli and M. avium complex. This should be taken into consideration before recommending discontinuation of mass BCG vaccination of newborns in areas with a high prevalence of M. avium complex infection.
Keywords: Mycobacterium avium-intracellulare Infection; Female; Infant; předškolní dítě; novorozenec; ženské pohlaví; Immune Tolerance; lidé; Infant, Newborn; Tuberculin Test; lymfadenitida; Incidence; intracelulární infekce bakterií Mycobacterium avium; Age Distribution; Male; tuberkulinový test; incidence; kojenec; Czech Republic; Child, Preschool; věkové rozložení; Česká republika; BCG vakcína; BCG Vaccine; imunologická tolerance; mužské pohlaví; Lymphadenitis; Humans